Factors associated with non-urgent visits to the emergency department in a tertiary care centre, western Saudi Arabia: cross-sectional study. Issue 10 (6th October 2020) - Al-Otmy, Saja S; Abduljabbar, Abeer Z; Al-Raddadi, Rajaa M; Farahat, Fayssal
Abstract : Objectives: To explore magnitude and factors associated with non-urgent visits to the emergency department (ED) in a tertiary care centre, western Saudi Arabia. Design: A cross-sectional study. Setting: ED of a tertiary care hospital in western Saudi Arabia. Participants: 400 patients, both men and women. Interventions: An interview-based questionnaire was administered to a consecutive sample of patients who visited the ED during morning shifts, where primary healthcare centres (PHCs) and outpatient clinics were available. Primary outcome measure: ED visits classified as non-urgent versus urgent (excluding life-threatening conditions) based on the Canadian Triage and Acuity Scale (CTAS). Levels IV and V were classified as non-urgent. Results: Majority of the cases were adult (97.3%) and half of them were women (54.8%). Non-urgent visits represented 78.5% among non-life-threatening cases. One-third of the patients (33.8%) had three visits or more to the ED during the past year. Main reasons for visiting the ED were perception that the condition was urgent (42.0%), easy access (25.5%) and limited resources and services at the PHCs (17.8%). Patients 40–50 years old were more likely to have non-urgent visits (OR=3.21, 95% CI 1.15 to 8.98). However, likelihood of non-urgent visits was significantly lower among patients with cancer (OR=0.37, 95% CI 0.19 to 0.72) and cardiovascular disease (OR=0.43, 95% CI 0.23 to 0.83), and those who live near the hospital (OR=0.49, 95% CI 0.28 to 0.88). Conclusions: The current study reported overuse of the ED. Enhancement of the primary care services, in concordance with community awareness, is an important component to reduce burden due to non-urgent use of the ED.